Cuidado desenvolvimental da teoria à prática do enfermeiro em unidade neonatal - Marski, Bruna de Souza Lima (2017)
Premature infants are usually referred to a Neonatal Intensive Care Unit and experience their initial development in this context. This environment has assistive technology that can assure its survival, but, paradoxically, it is also characterized as inhospitable, due to the effects of interventions performed there and the high sensorial load incompatible with the self-regulation capacity of those children. The nurse is directly related to care and is a mandatory requirement in the care context of the Neonatal Intensive Care Unit, it plays a fundamental role in the provision of qualified, humanized and integral care to the critical newborn and must consider the Developmental Care in their care practice. The present qualitative study aimed to analyze how the nurses incorporate in their care practice the Developmental Care to the preterm newborn hospitalized in the Neonatal Intensive Care Unit. The Symbolic Interactionism was listed as theoretical reference and Bardin Content Analysis was listed as methodological reference. The data gathering took place in a city in the interior of São Paulo, through non-participant observation, documentary research in medical records and semi-structured interviews. The triangulation of the findings was performed as the strategy for data analysis for qualitative research. Eleven nurses from the Neonatal Intensive Care Units of this city were subjects of this study. Data analysis resulted in the construction of five thematic categories: Developmental Care and Care Management; Developmental Care and Family; Developmental Care and Environment of the Neonatal Intensive Care Unit; Developmental Care and Pain; And Developmental Care and Skin. The nurses in this study have knowledge about most of the aspects involved in Developmental Care, recognize the same as relevant to a quality and safe practice for the critical newborn and his family and wish to broaden their presence in care practice. However, there are inconsistencies between the verbalized and the executed, as well as insufficiency in the record of its performance in relation to Developmental Care. It is concluded that Permanent Education emerges as a possible interventional resource to qualify and achieve transformations of care, to stimulate reflections about the practice of the Developmental Care in addition to strengthen the use of Nursing Care Systematization, aiming to contribute for an individualized and humanized care that meets the needs of the subjects.